A DISPUTE OVER LAND OWNERSHIP IN DAMPELAS: HEGEMONY OF DUTCH EAST INDIES AND BANAWA - Nadjamuddin, Lukman (History Department, Semarang State University and Historian Society of Indonesia, 2017)
This study affirms that the core issues of the land ownership disputes case in Dampelas region can be acknowledged, where land ownership is envisaged in the context of social, cultural and economic value. This research employs a historical method in which the source, including books, journals, archives, newspapers contemporaries, and research results. This study aims to explain the existence Dampelas which in the past was part of the Celebes Afdeling Midden located between two reigns, namely the Kingdom of Banawa in Donggala and Dutch East Indies in Batavia through their representatives in Makassar and Manado. In the late nineteenth and early twentieth century, this area became an important part of the Dutch East Indies in Banawa. The Dutch tried to take over the management of the potential of forest products Dampelas, without giving concessions to indigenous groups. In the reign of King Lamarauna, Kingdom of Banawa successfully suppress Dampelas without the cost and burden of war.Â Penelitian ini menegaskan bahwa isu-isu inti dari kasus sengketa kepemilikan tanah di wilayah Dampelas dapat diakui, di mana kepemilikan tanah ini dipertimbangkan dalam konteks nilai sosial, budaya dan ekonomi. Penelitian ini menggunakan metode sejarah di mana sumber, termasuk buku, jurnal, arsip, koran sezaman, dan hasil penelitian. Penelitian ini bertujuan untuk menjelaskan Dampelas keberadaan yang di masa lalu adalah bagian dari Afdeling Midden Celebes terletak di antara dua pemerintahan, yaitu Kerajaan Banawa di Donggala dan Hindia Belanda di Batavia melalui perwakilan mereka di Makassar dan Manado. Pada akhir abad kesembilan belas dan awal abad kedua puluh, daerah ini menjadi bagian penting dari Hindia Belanda di Banawa. Belanda mencoba untuk mengambil alih pengelolaan potensi hasil hutan Dampelas, tanpa memberikan konsesi kepada kelompok masyarakat adat. Pada masa pemerintahan Raja Lamarauna, Kerajaan Banawa berhasil menekan Dampelas tanpa biaya dan beban perang.Â